KRISIS EKONOMI, DISPARITAS, DAN PENANAMAN MODAL ASING - Yeru Salimianto; Anthoni Sriyatno (Muhammadiyah University Press, 2004)
By using Data Panel Model can be found the interprovincial disparity in Indonesia since 1997 until 1999, which caused by foreign investment. While the domestic investment, significantly do not influence to disparity. The disparity measured by Index Williamson was not big but that way remain to have to be made attention. Java and specially Capital Special District give a very big contribution to interprovincial disparity. As monetary and economic crisis precisely causes the disparity, become smaller. The weakness of this Data Panel Model there are low coefficient value of determination (R2) that is 26,3%. Other weaknesses lay in assumption that an equation slope of dummy variable is constant.